Biofortification: A Sustainable Solution to Hidden Hunger - , Harish Reddy C; , Nikita Kankanawadi; , Kruthika M. S.; , Shwetha G. V.; , Veenita M. K.; , Gagana Sindhu S (Archives of Current Research International, 2025)
Biofortification is a process of improving the nutritional quality of food crops by increasing their essential vitamins and minerals content like iron, zinc and vitamin A. This strategy is important especially for the people in developing countries who rely heavily on staple foods and often suffer from hidden hunger i.e., malnutrition caused by lack of micronutrients. Biofortified crops can be developed through traditional breeding, better agronomic practices, or modern genetic engineering. Several nutrient-rich varieties of rice, wheat, maize, sweet potato and other crops have been released in countries like India, Nigeria, Bangladesh etc. These crops offer long-term and cost-effective way to improve people’s health. However, issues such as taste, awareness, bioavailability of nutrients and market acceptance still need to be addressed. Future efforts should focus on combining multiple nutrients, using advanced breeding tools like CRISPR and promoting biofortified crops through national programs and public education. Overall, biofortification has great potential to make diets healthier and farming more sustainable.